Intervensi Nutrisi-Sensitif Dan Nutrisi-Spesifik Untuk Mengatasi Masalah Anak Stunting Di Aceh - Nanda Nur Sofyana (Politeknik Kampar, 2023)
Public health policy is important for reducing poverty as implemented by investing human capital such as in nutritional-sensitive and nutritional-specific programs. Indonesia is one of developing countries that has severe problems with stunted children, especially in the province of Aceh which currently has the highest percentage of stunting children. Thus, investment in human capital in nutritional intervention (specific and sensitive nutritional program) can be a solution to reduce a high percentage of stunting. According to many literature, the problem of poverty and malnutrition or stunted children can be overcome by nutritional and non-nutritional programs that should be carried out together so that nutritional problems can be addressed sustainably.